Socio-Economic Impacts of Tourism in India: An Empirical Analysis - ROUT, Himanshu B.; MISHRA, P. K.; PRADHAN, B. B. (Journal of Environmental Management and Tourism, 2017)
The importance of tourism as an instrument for economic growth and employment generation, particularly in remote and backward areas, has been well recognized world over. It is the largest service industry globally in terms of gross revenue as well as foreign exchange earnings. Tourism plays an effective role in achieving growth with equity objectives which we have set for ourselves. The extant tourism literature suggests that the expansion on tourism sector can contribute to long-run macroeconomic performance of developing countries. India ving high potential for the expansion of tourism industry can be a catalyst for the long-run socio-economic growth. Thus, we have investigated the impact of tourism on India’s economic growth over a period from 1990 to 2015. The results predict the possibility of long-run equilibrium relationship between tourism and economic growth. This justifies for the identification of the indicators which should be emphasized while formulating plans and policies for tourism sector expansion. The estimation of long-run regression model suggests that the indicators such as foreign exchange earnings, international tourists spending, domestic expenditure on tourism and capital investment by all industries related to travel and tourism are critical in making tourism industry an engine of economic growth.